2020
DOI: 10.7717/peerj.9606
|View full text |Cite
|
Sign up to set email alerts
|

The diet of otters (Lutra lutra) on the Agri river system, one of the most important presence sites in Italy: a molecular approach

Abstract: Background The Eurasian otter (Lutra lutra) underwent a strong decline in large areas of the Central-Western part of its distribution range, during the second half of the twentieth century. In Italy, only residual fragmented nuclei survive in the Central-Southern part of the peninsula. Nowadays, the otter is one of the most endangered mammals in Italy, and increasing the knowledge about the ecology of this species is a key step in defining fitting management strategies. Here we provide informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Our results are also in agreement with faecal DNA metabarcoding studies of otter diet. Both Buglione et al (2020) and Martínez-Abraín et al (2020) found fish were the primary food resource for otters, followed by amphibians. Specifically, Cyprinidae, Gobidae, Salmonidae and Percidae were the predominant prey taxa.…”
Section: Otter Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also in agreement with faecal DNA metabarcoding studies of otter diet. Both Buglione et al (2020) and Martínez-Abraín et al (2020) found fish were the primary food resource for otters, followed by amphibians. Specifically, Cyprinidae, Gobidae, Salmonidae and Percidae were the predominant prey taxa.…”
Section: Otter Dietmentioning
confidence: 99%
“…As such, DNA metabarcoding provides species resolution data at greater spatiotemporal scales for the vast majority of prey items, regardless of prey size, type and integrity or lack of hard components (Oehm et al 2011;Pompanon et al 2012;McInnes et al 2017;Forin-Wiart et al 2018;Traugott et al 2020). Since its inception, DNA metabarcoding has been employed to assess the diet of various mammalian predators (Shehzad et al 2012a(Shehzad et al , 2012b; De Barba et al 2014;Berry et al 2017;Gosselin et al 2017;Forin-Wiart et al 2018;Robeson et al 2018;Schwarz et al 2018) and recent small-scale studies have shown its potential for European otter (hereafter otter) diet analysis (Buglione et al 2020;Martínez-Abraín et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, its use has remained marginal (<10% of the scat-based carnivore diet analyses, Monterroso et al, 2019) and it has rarely been applied to top predators in tropical ecosystems (but see Havmøller et al, 2020) despite promising results on herbivores (Alberdi et al, 2019;Hibert et al, 2011;Mallott et al, 2018;Quéméré et al, 2013), hematophagous arthropods (Rodgers et al, 2017), or bats (Bohmann et al, 2018). This lack of studies on top predators in tropical compared to temperate areas (Deagle et al, 2010 on little penguins; Shehzad et al, 2012 on leopard cats;Kumari et al, 2019 andBuglione et al, 2020 on Eurasian otters) may be partly attributed to specific methodological issues. First, the efficiency of sDNA metabarcoding is highly dependent on the accuracy and completeness of reference DNA barcode databases (Alberdi et al, 2019;Zinger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As such, DNA metabarcoding provides species resolution data at greater spatiotemporal scales for the vast majority of prey items, regardless of prey size, type, and integrity or lack of hard components (Oehm et al 2011; Pompanon et al 2012; McInnes et al 2017; Forin-Wiart et al 2018; Traugott et al 2020). Since its inception, DNA metabarcoding has been employed to assess the diet of various mammalian predators (Shehzad et al 2012a, 2012b; De Barba et al 2014; Berry et al 2017; Gosselin et al 2017; Forin-Wiart et al 2018; Robeson et al 2018; Schwarz et al 2018), and recent small-scale studies have shown its potential for European otter (hereafter otter) diet analysis (Buglione et al 2020; Martínez-Abraín et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2018), and recent small-scale studies have shown its potential for European otter (hereafter otter) diet analysis (Buglione et al 2020;Martínez-Abraín et al 2020).…”
mentioning
confidence: 99%